Effect of poultry viscera meal inclusion in broiler diets in different rearing periods on performance, carcass and parts yields - Cruz, V C [UNESP]; Ducatti, C [UNESP]; Araújo, P C [UNESP]; Sartori, J R [UNESP]; Piccinin, A (Fundação APINCO de Ciência e Tecnologia Avícolas, 2009)
The objective of the present study was to evaluate the effect of the dietary inclusion of poultry viscera meal (VM) on broiler performance and carcass, parts, and abdominal fat yields in broilers by replacing a diet containing VM with a strictly vegetable diet and vice-versa. A number of 720 one-day-old broiler chicks were randomly distributed in 6 groups: G1-basal diet (BD) - corn and soybean based meal, with no VM from 1 to 42 days of age, G2- 8% VM diet from 1 to 42 days, G3- BD from 1 to 21 and 8% VM diet from 22 to 42 days, G4- BD from 1 to 35 and 8% VM diet from 36 to 42 days, G5- 8% VM diet from 1 to 21 days and BD from 22 to 42 days, G6- 8% VM diet from 1 to 35 and BD from 36 to 42 days. Average body weight, weight gain, feed intake, feed conversion ratio (FCR), production efficiency index, and mortality were determined from 1 to 42 days. There was no effect of treatments on performance or mortality, except for FCR, which was significantly better in the group fed VM from 1 to 35 days and withdrawn at the end of rearing (36-42 days). Also, there were no differences in carcass, parts, and abdominal fat yields, showing that VM in broiler diets does not influence yield parameters.
Keywords: Animal byproducts; broiler chickens; carcass yield; performance; poultry viscera meal